Evaluation Of Effectiveness Of Twin Block Appliance On The Anatomy Of Pharyngeal Airway Passage In Class Ii Malocclusion (International Journal of Environmental Sciences, 2025)
Background: Respiratory function and craniofacial development have been extensively studied, influencing orthodontic diagnosis and therapy. Functional appliances aid mandibular anterior relocation, according to research. One third of the population has Class II Skeletal malocclusion because of mandibular retrusion, according to some studies. Twin Block appliances (TB) are popular functional appliances because they can cause rapid growth changes. Hence the study aimed to evaluate the pharyngeal airway space effect after administration of the Twin block applianceMethodology: A retrospective investigation conducted in a hospital setting, focusing on patients aged 8-14 with skeletal Class II malocclusion. Using convenience sampling, A total of 38 individuals were identified and split into two groups of 19. The project was approved ethically before it began.A twin block appliance was given to the treatment group, while pre-orthodontic treatment was given to the control group. To assess alterations in the pharyngeal airway space, lateral cephalograms were examined at baseline and six months later. SPSS was used for statistical analysis, and paired and independent t-tests were used to evaluate changes before and after therapy, with p<0.05 being deemed significant.Results: The treatment group showed significant decreases in SNA and increases in SNB, indicating effective mandibular advancement and improved airway dimensions, while maxillary length remained unchanged. In contrast, the control group exhibited maxillary growth but no significant changes in SNA. Airway measurements decreased in the control group, highlighting airway constriction. Overall, the Twin Block group demonstrated superior outcomes in mandibular advancement and airway improvement compared to the control group.Conclusion The study confirms the Twin Block's effectiveness in correcting Class II malocclusion and improving airway dimensions, emphasizing its benefits for dental and systemic health in pediatric orthodontics.